Analisis Pemahaman Masyarakat Terhadap Zakat Pertanian Di Desa Duko Timur Kecamatan Larangan Kabupaten Pamekasan - Itsnawati, Try; Nisa’, Nafilatun Khairun; Fadllan, Fadllan; Aprianto, Mohammad Andri Dwi; Vitriyah, Nurul Lailatul (Publikasi Penelitian Terapan dan Kebijakan, 2025)
Zakat must be paid if the agricultural produce reaches the nisab. This zakat is known as agricultural zakat. Agricultural zakat is closely related to the welfare of the community which can help reduce poverty levels if its distribution is right on target. The purpose of this study was to determine the perception of the people of Duko Timur Village towards agricultural zakat. This research method is a qualitative research method. with data collection including documentation, interviews, surveys, and observations. Based on the results of the study, it shows that: residents of Duko Timur Village still have a basic understanding of agricultural zakat, namely only knowing its meaning. The understanding of the people of Duko Timur Village is only equivalent to alms or what is known as "salametan" for agricultural products. The importance of public education needs to be carried out because low literacy regarding agricultural zakat is the root cause of low public knowledge.